Az európai közigazgatás főszereplője: az Európai Bizottság (The protagonist of European public administration: the European Commission) - András Torma (KözigazgatásTudomány)
The European Union, established by the Maastricht Treaty concluded in 1992, implemented and continues to implement cooperation between (nation) states unprecedented in world history. The EU is not a classic international organization, nor it is a federal state, somewhere between the two categories of public law. The same special public law situation can be demonstrated in the EU institutional system as a whole, but especially in the case of the European Commission, the key actor of European public administration. The dissertation presents the Commission's history, tasks and powers, organizational structure and operation, and then draws the necessary conclusions. Are you looking for an answer to the question of whether the Commission, as the protagonist of European public administration, is the engine of integration, as in the past, or rather as an enforcer of self-interests, rather a brake on it, or perhaps a role model for illegal operation?